2005
DOI: 10.1161/circulationaha.104.526749
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled Cell Distribution After Intramyocardial, Intracoronary, and Interstitial Retrograde Coronary Venous Delivery

Abstract: Background— Several clinical studies are evaluating the therapeutic potential of delivery of various progenitor cells for treatment of injured hearts. However, the actual fate of delivered cells has not been thoroughly assessed for any cell type. We evaluated the short-term fate of peripheral blood mononuclear cells (PBMNCs) after intramyocardial (IM), intracoronary (IC), and interstitial retrograde coronary venous (IRV) delivery in an ischemic swine model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(64 citation statements)
references
References 32 publications
1
63
0
Order By: Relevance
“…Consequently, MSCs have become the cell of choice for therapeutic use in tissue repair [5]. However, a review of studies conducted in the last two decades suggests that a limiting factor for MSC-based therapy is the engraftment of low number of MSCs (0.44-1%) [3,10] in damaged sites and lack of understanding of the mechanisms involved in MSCs engraftment [11]. There is a consensus that strategies that would improve MSCs homing and engraftment are required to optimize their therapeutic use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, MSCs have become the cell of choice for therapeutic use in tissue repair [5]. However, a review of studies conducted in the last two decades suggests that a limiting factor for MSC-based therapy is the engraftment of low number of MSCs (0.44-1%) [3,10] in damaged sites and lack of understanding of the mechanisms involved in MSCs engraftment [11]. There is a consensus that strategies that would improve MSCs homing and engraftment are required to optimize their therapeutic use.…”
Section: Discussionmentioning
confidence: 99%
“…Although attractive, a major limitation of MSCs therapy is the low engraftment yield of transplanted cells in infarcted zones; approximately only 0.44% of transplanted MSCs reside in the myocardium after 4 days [3,10]. Moreover, direct intra-cardiac delivery of MSCs does not substantively increase their engraftment yield (range 1-3%) [11]. Clearly, a better understanding of MSCs biology is required to optimize MSCs therapy [12].…”
Section: Introductionmentioning
confidence: 99%
“…The cardiac patch developed requires open-heart surgery to implant the patch, either by suturing [164,165] or by applying bioglue to the patch [166]. A PCL/gelatin patch incorporated with MSCs activated endogenous cardiac repair by enhancing the survival of MSCs and their HIF-1a, Tb4, VEGF, and SDF-1 expression and decreased CXCL14 expression in hypoxic and serum-deprived conditions.…”
Section: (A) Invasive Methodsmentioning
confidence: 99%
“…For example, early studies in an ischemic swine model demonstrated retention rates of peripheral blood mononuclear cells within the myocardium of only about 2.6%, 3.2%, and 11% after intracoronary, interstitial retrograde coronary venous, and intramyocardial delivery, respectively [127]. For these low retention rates, some of the delivery routes are controversially discussed regarding their actual impact on the recovery of cardiac function [126,128].…”
Section: Delivery and Final Fatementioning
confidence: 99%